Understanding the circular economy in Europe, from resource efficiency to sharing platforms: the CEPS framework - Taranic, Igor; Behrens, Arno; Topi, Corrado (Brussels, 2016)
"This paper aims to rethink the concept of the ‘circular economy’ through the prism of its relevance to its many stakeholders, ranging from public and private actors and mature and emerging industries to cities and regions, SMEs and multi-sectoral corporations. The paper presents a schematic framework, which breaks down the circular economy into eight fundamental building blocks and shows how they are interconnected in relation to the multiplicity of involved actors. Coincidentally called “CEPS” (short for Circular Economy Progress for Stakeholders), the framework is used to develop recommendations addressed to European policy-makers on how best to support the transition towards a circular economy in the EU."